In vitro characterization of fiber-rich tropical feedstuffs for pig diets (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study aimed to characterize the characteristics of fiber-rich feedstuffs using a three-step in vitro method. Materials and methods: A three-step in vitro digestibility simulation included step 1 and step 2, which were referred to as “enzymatic hydrolysis” and mimicked processes in the stomach, followed by an ileal digestibility assessment, whereas step 3 mimicked the hindgut fermentation using fecal inoculum. The fiber-rich feedstuffs used were banana stem (Musa acuminata) (Bas), brewery by-product (Brew), cassava (Manihot esculenta) leaf (CL) and root by-product, cabbage waste (Brassica oleracea) (Caw), sweet potato vines (Ipomoea batatas) (Swe), taro leaves and petioles (Colocasia esculenta) (Taro), tofu by-product (TF), and Trichanthera gigantea foliage (Tri). Results: Tri and TF were marginally (10%) digested in the small intestine; for TF, this was largely compensated for by the level of the hindgut, resulting in the highest volatile fatty acid (VFA) production from TF as compared with any other fiber-rich feedstuff tested. Nevertheless, 55% of the crude protein (CP) of TF was digested in the small intestine, resulting in a modest accumulation of hindgut ammonia as compared with CP from Tri, which particularly seemed to be fermented in the hindgut. For the complete diets, the ileal digestible CP of the test diets was 7.8% to 18.5% lower than that of the control diet, except for the TF diet. Only diets including Bas and CL enhanced hindgut VFA production compared with the control. Conclusion: Fiber-rich feedstuffs differ widely in intestinal digestibility and hindgut fermentation. The three-step in vitro simulation results for the nine tested fiber-rich feedstuffs could provide valuable insights into assessing feeding values for pig production. Additionally, an interaction was observed between fiber source and dietary nutrients in complete diets, which impaired ileal CP digestibility.J. Adv. Vet. Anim. Res., 12(4): 1354–1362, December 2025http://doi.org/10.5455/javar.2025.l995